Problems of State Programs Forming - Anatoly Yakovlevich Zaporozhan (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article is devoted to consideration of a perspective of state programs forming. The state program is a difficult planned document. The success of aprogram implementation is pledged by forming of its content. In the article based on the analysis of a number of state programs the positive and negative moments of their content are considered.